PERBANKAN SYARIAH SEBAGAI SOLUSI UNTUK PERMASALAHAN KEMISKINAN DI INDONESIA - OKTAFIA, ERVI (Jurnal Akuntansi AKUNESA, 2014)
Poverty is a serious problem faced by the Indonesian state, although many efforts have been made by the government but the level of poverty is still very high. Islamic banking in Indonesia, beginning Attendance is expected to be the main solution to the problem of poverty in this country. Islamic banking is a banking system that was developed based on Islamic law. Businesses based on the establishment of this system in the Islamic religious prohibition to levy or borrow with interest or so-called usury and investment restrictions for businesses categorized forbidden. Even that is quite unique in Indonesia with the Islamic Banking Act, the two concepts, namely social commercial and financial institutions can be done by either its Islamic banking or non-bank Bank. Thus developing Islamic economics through the Islamic finance as part of efforts to eradicate poverty. Keywords: Islamic banking, Poverty, Banking system